Pengembangan Unit Usaha Pesantren Produksi Sabun Cair Dayah Darusa'adah - Nasri; Zubaili (BA: Jurnal Pengabdian kepada Masyarakat, 2024)
This community engagement program aims to develop a pesantren-based business unit through the production of liquid soap as an effort to enhance economic self-sufficiency at Dayah Darusa’adah, located in Gampong Lhok Panjoe, Darul Ihsan Subdistrict, East Aceh Regency. The implementation method included several stages: business feasibility analysis, production planning, skills training, facility development, and marketing strategy. The results indicate that the business unit successfully produced liquid soap independently, involved students (santri) in the production process, and began local product distribution. However, several challenges were encountered, including limited capital, production facilities, and product legality. Despite these obstacles, the program has had a positive impact on empowering students and the surrounding community, marking an important step toward building an economically self-reliant pesantren.